Introduction to linear algebra and the theory of matrics - Schwerdtfeger, Hans (Holland Groningen, 1961)
Linear algebra is a branch of mathematics that studies vectors, vector spaces (also known as linear spaces), linear transformations, and systems of linear equations. Matrices are fundamental tools in linear algebra, serving as rectangular arrays that represent linear transformations and systems of equations.
Keywords: Linear algebra; Theory of matrices; Mathematics